Design of a Novel Efficient High-Gain Ultra-Wide-Band Slotted H-Shaped Printed 2×1 Array Antenna for Millimeter-Wave Applications with Improvement of Bandwidth and Gain via the Feed Line and Elliptical Edges - Tibermacine Badreddine; Hamaizia Zahra; Guesbaya Tahar (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
This paper describes design procedure of a high-performance miniaturized antenna with an array configuration, which contributes to enhancing the communication system’s performance. The basic antenna features a compact size (6 x 6) mm2, and its single element is an H-shaped slotted patch printed on the top side of a Rogers RT5880 substrate, with a relative permittivity and thickness of 2.2 and 0.3 mm, respectively. The edge-to-edge distance of the 2 × 1 array antenna is 9 x 14 mm2, and the isolation between its radiation elements is 4.5 mm. To increase the capabilities of the antenna in terms of gain and bandwidth, we proceeded to use the 2 × 1 array configuration and then optimized the model via either the width of the feed line or the elliptical edges of the patch. The miniaturized array antenna achieved a peak gain of 12.56 dB, a directivity of 13.11 dBi, and a return loss of -47.52 dB at a resonance frequency of 91.5 GHz, with a radiation efficiency of more than 91% over an operating bandwidth of 15.83 GHz, ranging from 79.7 GHz to 95.6 GHz. The design and simulation results of the proposed antenna were obtained using the CST Studio software.